Presynaptic Boutons That Contain Mitochondria Are More Stable - Lees, Robert M.; Johnson, James D.; Ashby, Michael C. (Frontiers in Synaptic Neuroscience, 2020)
Addition and removal of presynaptic terminals reconfigures neuronal circuits of the mammalian neocortex, but little is known about how this presynaptic structural plasticity is controlled. Since mitochondria can regulate presynaptic function, we investigated whether the presence of axonal mitochondria relates to structural plasticity of presynaptic boutons in mouse neocortex. We found that the overall density of axonal mitochondria did not appear to influence loss and gain of boutons. However, positioning of mitochondria at individual presynaptic sites did relate to increased stability of those boutons. In line with this, synaptic localisation of mitochondria increased as boutons aged and showed differing patterns of localisation at en passant and terminaux boutons. These results suggest that mitochondria accumulate locally at boutons over time to increase bouton stability.